Environmental controls of marine productivity hot spots around Antarctica1. Issue 8 (11th August 2015) - Arrigo, Kevin R.; van Dijken, Gert L.; Strong, Aaron L.
Abstract Antarctic coastal polynyas are biologically rich ecosystems that support large populations of mammals and birds and are globally significant sinks of atmospheric carbon dioxide. To support local phytoplankton blooms, these highly productive ecosystems require a large input of iron (Fe), the sources of which are poorly known. Here we assess the relative importance of six different environmental factors in controlling the amount of phytoplankton biomass and rates of net primary production (NPP) in 46 coastal polynyas around Antarctica. Data presented here suggest that melting ice shelves are a primary supplier of Fe to coastal polynyas, with basal melt rates explaining 59% of the between‐polynya variance in mean chlorophyll a (Chl a) concentration. In a multiple regression analysis, which explained 78% of the variance in chlorophyll a (Chl a) between polynyas, basal melt rate explained twice as much of the variance as the next most important variable. Fe upwelled from sediments, which is partly controlled by continental shelf width, was also important in some polynyas. Of secondary importance to phytoplankton abundance and NPP were sea surface temperature and polynya size. Surprisingly, differences in light availability and the length of the open water season explained little or none of the variance in either Chl a or NPP between polynyas. If the productivity of coastal polynyas is indeed sensitive to the release of Fe from melting ice shelves, future changes in ice shelf melt rates could dramatically influence Antarctic coastal ecosystems and the ability of continental shelf waters to sequester atmospheric carbon dioxide.